P53 impairs endothelial function by transcriptionally repressing Kruppel-like factor 2 - Kumar, Ajay (2010)
OBJECTIVE: Endothelial Kruppel-like factor 2 (KLF2) mediates endothelium-dependent vascular homeostasis by differentially regulating endothelial genes, leading to an anti-inflammatory and anti-thrombotic endothelial surface with normal vasodilatory function. In contrast, the tumor suppressor p53 leads to inflammatory gene expression and impairs endothelium-dependent vasodilatation, thus promoting endothelial dysfunction. We asked whether p53 decreases KLF2 expression, and determined whether p53-mediated suppression of KLF2 plays a role in p53-induced endothelial dysfunction. METHODS AND RESULTS: The effect of p53 on KLF2 expression was determined. P53 inhibited KLF2 transcription in a histone deacetylase-dependent and histone acetyltransferase-independent fashion. KLF2 expression was suppressed by p53 via a conserved p53-binding repressor sequence in its promoter. P53 bound to, and stimulated deacetylation of histone-3 at, the KLF2 promoter. The effect of p53 on endothelial KLF2 target genes was examined. Down-regulation of p53 increased expression of endothelial nitric oxide synthase (eNOS) and thrombomodulin(TM), while inhibiting expression of plasminogen activator inhibitor 1 (PAI-1). Conversely, overexpression of p53 suppressed eNOS and TM expression, and stimulated PAI-1 and endothelin-1 (ET-1) expression. Knockdown of KLF2 abolished p53-induced decrease in TM, and increase in ET-1 expression. Both, overexpression of p53 and knockdown of KLF2 in endothelial cells, increased blood coagulation on an endothelial cell monolayer. P53-induced increase in coagulation was rescued by forced expression of KLF2. P53 also impaired endothelium-dependent vasodilatation and decreased bioavailable vascular nitric oxide, both of which were rescued by forced KLF2 expression. CONCLUSIONS: These findings illustrate a novel p53-dependent mechanism for the regulation of endothelial KLF2 expression. In addition, they show that down-regulation of KLF2, in part, mediates a p53-stimulated dysfunctional endothelium.